The Digital Library of the Middle East and Implementing International Cultural Heritage Preservation Policy - Herdrich, Peter (KULA)

(untitled) (University of Victoria Libraries, 2018)
This article reviews the origins and goals of the Digital Library of the Middle East and discusses how the DLME and other digital library projects implement international cultural heritage preservation policy.